Migrating leukocytes are the source of Peroxiredoxin V during inflammation in the airways - Kropotov Andrei V; Krutilina Raisa I; Leutenegger Christian; Serikov Vladimir B (BMC, 2006)
Abstract Background We characterized changes in expression of the antioxidant protein Peroxiredoxin V (PRXV) during airway inflammation. Methods Studies in anesthetized rats and mice; PRXV expression determined by Western blot analyses and immunohistochemistry; PRXV m-RNA expression determined by Taq-Man RT-PCR. Results Bacterial lung inflammation did not change expression of PRXV in murine epithelia but produced massive influx of leukocytes highly expressing PRXV. Endotoxin and f-MLP induced leukocyte migration in rat trachea but did not change mRNA levels and PRXV protein expression in tracheal epithelial cells. In primary airway cell culture (cow), alveolar epithelial cells A549, or co-culture of A549 with murine macrophages RAW264.7, exposure to live bacteria increased expression of PRXV, which required serum. PRXV was secreted in vitro by epithelial and immune cells. Conclusion Inflammation increased expression of PRXV in airways by at least 2 mechanisms: cell population shift by massive influx of leukocytes expressing PRXV, and moderate post-transcriptional up-regulation of PRXV in epithelial cells.